정치적 소통 만족에 영향을 미치는 요인에 관한 연구 -정치적 성향과 미디어 이용을 중심으로 - 김미선; Kim, Mi-Sun (한국콘텐츠학회 논문지, 15(5), 2015)
This study discusses on the influential factors of satisfaction in communication by focusing on the political communication phenomenon that is revealed in our society. The acts of political communication and its communication satisfaction are examined by exploring individuals' political inclination and their media usage which are the main influential factors of political communication. An interview survey was conducted on a thousand adults over the age of nineteen who are residing in sixteen cities and provinces nationwide. As a result, a high rate of online media usage was observed among people with progressive political inclination. It showed that the political communication acts of 'writing/communicating' which indicates ons actively posting their personal opinions, has a positive influence on communication satisfaction. On the other hand, the usage of offline media was dominant over people with conservative and neutral political inclination. A passive act of 'reading/watching,' which is to observe other people's opinions, was shown by most of the interviewees. Therefore, it was able to discuss that in order for a harmonious flow of political communication among our society, the understanding of citizens' political characteristic must be preceded and the differentiated political communication using media must be raised accordingly. 본 연구는 우리 사회에서 나타나는 정치적 소통 현상에 주목하여 소통 만족에 영향을 미치는 요인을 논의하였다. 정치적 소통의 주요 영향요인으로 개인의 정치적 성향과 미디어 이용을 살펴봄으로써 정치 커뮤니케이션 행위와 정치적 소통 만족도를 평가했다. 전국 16개 시도에 거주하는 만19세 이상 성인 1000명을 대상으로 면접원 설문조사를 실시한 결과, 진보적 정치성향은 온라인 미디어 이용이 많았으며, 개인의 의견을 적극 게재하는 '쓰기/대화'의 정치 커뮤니케이션 행위가 소통 만족에 긍정적인 영향을 미치는 것으로 나타났다. 반면 보수, 중도적 정치성향은 오프라인 미디어를 주로 이용하였고, 타인의 의견을 살피는 '읽기/시청'의 소극적 정치 커뮤니케이션 행위가 중점적으로 나타났다. 따라서 우리 사회에서 정치적 소통을 원활히 하기 위해서는 시민의 정치적 특성에 대한 이해가 선행되어야 하며, 이에 따른 차별화된 미디어 활용 정치커뮤니케이션이 제고되어야 함을 논의할 수 있었다.